Anti-disturbance control for time-varying delay Markovian jump nonlinear systems with multiple disturbances. Issue 15 (18th November 2017) - Li, Yankai; Sun, Haibin; Zong, Guangdeng; Hou, Linlin
ABSTRACT: In this paper, the problem of composite anti-disturbance resilient control is addressed for time-varying delay Markovian jump nonlinear systems with multiple disturbances. The disturbances are assumed to include two parts: the first one in the input channel is described by an external system with perturbations; the second one is supposed to be bounded H 2 norm. By combining disturbance observer and L 2 – L ∞ control method, the disturbances are attenuated and rejected, simultaneously, and the desired dynamic performance can be obtained for time-varying delay Markovian jump nonlinear systems. Moreover, the gains of the resilient controller and the observer are acquired by applying linear matrix inequalities (LMIs) technology. Finally, an application example is presented to show the effectiveness of the proposed approach.